Leucodellus Reuter, 1906 (Heteroptera: Miridae: Phylini): key to species, revised species composition and diagnosis - Konstantinov, Fedor V. (Zootaxa, 2012)
Leucodellus is redefined to include six species and an updated diagnosis is given for this phyline genus. Illustrated keyand diagnoses for all species are provided. The genus Leucophylus Duwal, Yasunaga & Lee is synonymized with Leucodellus Reuter, 1906. L. nathaliae Josifov, 1974 is transferred to the genus Compsidolon Reuter, 1899.